Treatment Strategies for GLILD in Common Variable Immunodeficiency: A Systematic Review - Lamers, Olivia A. C.; Smits, Bas M.; Leavis, Helen Louisa; de Bree, Godelieve J.; Cunningham-Rundles, Charlotte; Dalm, Virgil A. S. H.; Ho, Hsi-en; Hurst, John R.; IJspeert, Hanna; Prevaes, Sabine M. P. J.; Robinson, Alex; van Stigt, Astrid C.; et al. (Frontiers in Immunology, 2021)
Introduction: Besides recurrent infections, a proportion of patients with Common Variable Immunodeficiency Disorders (CVID) may suffer from immune dysregulation such as granulomatous-lymphocytic interstitial lung disease (GLILD). The optimal treatment of this complication is currently unknown. Experienced-based expert opinions have been produced, but a systematic review of published treatment studies is lacking. Goals: To summarize and synthesize the published literature on the efficacy of treatments for GLILD in CVID. Methods: We performed a systematic review using the PRISMA guidelines. Papers describing treatment and outcomes in CVID patients with radiographic and/or histologic evidence of GLILD were included. Treatment regimens and outcomes of treatment were summarized. Results: 6124 papers were identified and 41, reporting information about 255 patients in total, were included for review. These papers described case series or small, uncontrolled studies of monotherapy with glucocorticoids or other immunosuppressants, rituximab monotherapy or rituximab plus azathioprine, abatacept, or stem cell transplantation. Treatment response rates varied widely. Cross-study comparisons were complicated because different treatment regimens, follow-up periods, and outcome measures were used. There was a trend towards more frequent GLILD relapses in patients treated with corticosteroid monotherapy when compared to rituximab-containing treatment regimens based on qualitative endpoints. Conclusions: We could not draw definitive conclusions regarding optimal treatment for GLILD in CVID from the current literature since quantitative, well-controlled evidence was lacking. Our findings highlight the need for further research with uniform, objective and quantifiable endpoints. This should include international registries with standardized data collection including regular pulmonary function tests (with carbon monoxide-diffusion), uniform high-resolution chest CT radiographic scoring, and uniform treatment regimens, to facilitate comparison of treatment outcomes and ultimately randomized clinical trials.